Dakwah Melalui Syi’ir: Alternatif Metode Dakwah pada Masyarakat Urban - Prianto, Agung Teguh (STID Al-Hadid, 2023)
DAKWAH THROUGH SYI'IR: ALTERNATIVE DAKWAH METHODS IN URBAN SOCIETY. Urban growth and the dynamics of urban society indicate significant changes in people's mindsets, lifestyles and values. This raises new challenges for the development of da'wah methods that can be relevant and effective in this complex and diverse urban society. One alternative method of da'wah that has emerged is the use of syi'ir, a form of Islamic literature that combines religious messages with aesthetic beauty. History proves that the acceptance of da'wah through syi'ir is able to change beliefs that have been rooted in Indonesian society for hundreds of years. Hindu and Buddhist beliefs have been replaced by embracing Islam through syi'ir preached by the Walisongo in Indonesia. This research method uses a qualitative approach with a library research design, this study will explore the phenomena of change in society caused by the acceptance of Islamic concepts with existing poetry approaches, as well as looking for historical data on how people can change their beliefs through syi’ir. The results of this research are to explore the potential to using syi'ir as a method of da'wah among urban communities. Analyzing the impact of syi'ir in forming religious understanding and moral values in urban society. As well as assessing the community's response and acceptance of da'wah through syi'ir